Design and Implementation of Single Sided Deafness Treatment Device - Mohammed, Israa Saeb; Jassim, Rana Hameed (American Journal of Biomedicine and Pharmacy, 2024)
This project aims to design and implement a device that helps people who suffer from unilateral deaf problems through, where this device is installed on the affected ear of the person and then the device receives the sounds coming from the surrounding environment and then transfers them to the healthy ear on the other end and this is done using technicians It's called CROS (Contralateral Routing of Signals). With a CROS system, you wear hearing aids on both ears, even though you can’t hear in one of them. The sound detected by the aid on the "bad ear" is transmitted directly to the aid on the "good ear" side. This gets rid of the “head shadow” effect.